Identification of Simple Sequence Repeat Markers(SSR) Specific for Thermo-Sensitive Genic Male Sterile Rice Lines and Their Utilization in Assessment of Seed Purity - Sangarwut, Numphet; Thanananta, Theerachai; Chakhonkaen, Sriprapai; Tongmark, Keasinee; Panyawut, Natjaree; Sikaewtung, Kannika; Wasinanon, Thiwawan; Muangprom, Amorntip (Thai Journal of Science and Technology, 2022)
Genetic purity is a key for hybrid rice seed production. Genetic purity of parental lines is an important factor affecting the genetic purity of the hybrid seeds. In this study, SSR markers specific for the thermo-sensitive genic male sterile (TGMS) rice lines were identified and used to assess their seed purity. A total of 40 SSR markers distributed on 12 rice chromosomes were used for genotyping 3 TGMS rice lines (IR68301-11-6-4-4-3-6-6, IR76761-4-3-17-34-35, and IR75589-31-27-8-33) obtained from international rice research institute (IRRI), and 20 Thai elite rice verities/lines. The results showed that RM341 was specific for IR68301-11-6-4-4-3-6-6. Four SSR markers (RM1359, RM1362, RM408, and RM219) and three SSR markers (RM190, RM225 and RM21) were specific for IR76761-4-3-17-34-35, and IR75589-31-27-8-33, respectively. In addition, SSR markers specific for eight Thai elite rice verities/lines were identified. The SSR markers specific for each TGMS line were used to determine their seed purity. Seed impurities were detected in 2 out of the 3 TGMS lines, suggesting the precaution for maternal seed production. These markers will be helpful for cultivar identification, seed purity test, intellectual property right (IPR), and future rice breeding programs.